Creeping Along the Guanxian‐Anxian Fault of the 2008 Mw 7.9 Wenchuan Earthquake in the Longmen Shan, China. Issue 7 (21st July 2018) - He, X. L.; Li, H. B.; Wang, H.; Zhang, L.; Xu, Z. Q.; Si, J. L.
Abstract: Crustal active faults can slip either steadily by aseismic creep, or abruptly by earthquake rupture. Creep can continuously relax the stress and reduce the magnitude of earthquakes. Identifying the slip behavior of active faults plays a crucial role in predicting and preventing earthquake disasters. Here we carried out multiscale structural analyses of fault rocks from the Guanxian‐Anxian fault zone (GAF) surface rupture of the 2008 Mw 7.9 Wenchuan earthquake (Longmen Shan thrust belt, China), and from the 3rd pilot borehole of the Wenchuan earthquake Fault Scientific Drilling project (WFSD‐3P). Results revealed that distributed R1 shears, pressure solution seams, partly dissolved clasts and mineral grains (e.g., quartz and albite), and newly formed phyllosilicate minerals all prevail in the clay‐rich fault rocks at different depths. Microstructural observations combined with X‐ray diffraction analysis show that the majority of clay minerals in the fault gouges were newly formed by pressure solution. The growth of new phyllosilicates prevents soluble grains from coalescing, thereby maintaining fast diffusive paths along solution seams, which promotes the formation of pressure solution. Both weak phyllosilicate minerals and pressure solution can control aseismic creep. Therefore, the slip behavior of the GAF is dominated by long‐term aseismic creep due to the interplay between new phyllosilicate minerals and pressure solution. Based on P wave velocity and strata distribution, we propose a model in which the GAF is creeping at shallow depths and locked at greater depths, as a possible explanation for the Wenchuan earthquake rupture mechanism. Key Points: Structures of the fault rocks indicate that the Guanxian‐Anxian fault zone (GAF) of the 2008 Mw 7.9 Wenchuan earthquake has a creeping behavior The creep of the GAF is mainly attributed to the interplay between newly formed phyllosilicate minerals and pressure solution The GAF is creeping at shallow depths and locked at deep, which provides a possible explanation for the Wenchuan earthquake rupture